Web-Based CRM Implementation for Improving Agricultural Product Sales Strategy: A Case Study of UD. Sri Tani - Husnul Khotimah; Mardalius Mardalius; Muhammad Bayu Al Dhana (Jurnal IPTEK Bagi Masyarakat, 2026)
The development of information technology encourages business actors, including Micro, Small, and Medium Enterprises (MSMEs), to utilize information systems to improve operational efficiency and customer relationship management. Customer Relationship Management (CRM) is a strategy used to manage interactions with customers in order to increase customer satisfaction and loyalty. However, many MSMEs still record customer data and sales transactions manually, resulting in less effective data management processes. UD Sri Tani is a business engaged in the sale of agricultural products that still manages customer data, product inventory, and sales transactions manually. This condition causes difficulties in monitoring customer relationships and developing effective sales strategies. Therefore, this study aims to implement a web-based Customer Relationship Management (CRM) system to improve customer management and support sales strategies. The research method used includes system requirements analysis, system design, system implementation, and system testing. Data collection was conducted through observation, interviews, and the distribution of questionnaires to 39 respondents consisting of customers and business managers. System testing was carried out using the Black Box Testing method to ensure that all system functions operate according to user requirements. The results of the study indicate that the developed CRM system is capable of integrating customer data, product data, and sales transactions in a centralized manner. Based on 15 testing scenarios, all system functions showed a 100% success rate, indicating that the system operates properly according to user needs. The implementation of this system helps business owners manage customer relationships more effectively and supports the improvement of agricultural product sales strategies at UD Sri Tani.